Isotonic Saline Nebulization and Lung Function in Children With Mild Respiratory Ailments - Barski, P; Surdacki, M; Saj, A; Wróblewska, A; Ornat, M; Pawelak, A; Pompa, D; Jurgiel, J; Ermisch, V; Hirnle, A; Pirogowicz, I; Stanisławska, I; et al. (Physiological research, 2020)
Nebulization with saline solution, although commonly used to alleviate respiratory symptoms, particularly in children, is often questioned concerning its effectiveness. In this study, we investigated the effects of isotonic saline nebulization on lung function in 40 children (mean age of 14±1 years) suffering from different types of airway disorders. Measurements were carried out directly before and up to 15 min after nebulization, for six days in a row, always on the same day time in the morning. The children were divided into two study groups according to the baseline ratio of forced expired volume in one second/forced vital capacity (FEV1/FVC), below and above 80 %. We found significant improvements after saline nebulization in FEV1, mid-expiratory flow at 50 % and 75 % of FVC (MEF50 and MEF75), and peak expiratory flow (PEF) in the group with the baseline FEV1/FVC less than 80 %. In contradistinction, children with an index greater than 80 % displayed no appreciable changes in the lung function variables when compared with the baseline level before saline nebulization. We conclude that isotonic saline nebulization might mitigate the functional signs of threatening pulmonary obstruction and as such may be clinically useful in pediatric patients with mild respiratory problems.
Keywords: respirační funkční testy; usilovný výdechový objem; Saline Solution; Humans; mechanika dýchání; Forced Expiratory Volume; Female; Lung; lidé; Respiratory Function Tests; nebulizátory a vaporizátory; poruchy dýchání; plíce; solný roztok; ženské pohlaví; Respiratory Mechanics; Male; Adolescent; mužské pohlaví; Respiration Disorders; Nebulizers and Vaporizers; mladiství